Oxidative imbalance as a co-player in jaw functional limitations and biopsychosocial profile in patients with temporomandibular disorder—myofascial pain with referral - Joanna Kuć; Krzysztof Dariusz Szarejko; Mateusz Maciejczyk; Violetta Dymicka-Piekarska; Małgorzata Żendzian-Piotrowska; Anna Zalewska; Anna Zalewska (Frontiers in Neurology, 2025)
IntroductionTemporomandibular disorders have a multifactorial etiology including biological, biomechanical, neuromuscular, and biopsychosocial factors. Current research on temporomandibular disorders focuses on identifying clinically relevant biomarkers thus creating a new way of thinking about this dysfunction. The aim of the study was to determine the relationship between salivary/blood concentrations of oxidative/nitrosative stress biomarkers and biopsychosocial findings in patients with temporomandibular disorder—myofascial pain with referral.MethodsThe sample enrolled a total of 26 individuals with temporomandibular myofascial pain with referral (twenty women, six men). The procedure included clinical examination according to the Diagnostic Criteria for Temporomandibular Disorders, saliva and blood collection. Biochemical analysis concerned, among others, the content of reduced glutathione, uric acid, total antioxidant capacity, advanced glycation end products, malondialdehyde, total lipid hydroperoxides, kynurenine, N-formylkynurenine, and peroxynitrite. All determinations were considered with respect to the Patient Health Questionnaire-4 (PHQ-4), Patient Health Questionnaire-9 (PHQ-9), Patient Health Questionnaire-15 (PHQ-15), Generalized Anxiety Disorder-7 (GAD-7), Jaw Functional Limitation Scale-20 (JFLS-20), Perceived Stress Scale-10 (PSS-10), and Beck Depression Inventory (BDI).Results and discussionThe average age of participants was 24.2 ± 1.23. High content of kynurenine and N-formylkynurenine in plasma was related to intensified psychological distress (PHQ-4) and anxiety (GAD-7). Low concentration of plasma malondialdehyde and total lipid hydroperoxides was linked with severe somatization (PHQ-15) and stress (PSS-10), respectively. Reduced levels of non-enzymatic antioxidants were associated with greater jaw functional mobility restrictions as well as limited mastication and communication factor with respect to JFLS-20. These findings indicate that oxidative stress biomarkers are significantly related to the biopsychosocial profile in patients with temporomandibular disorder.